2017
DOI: 10.1186/s12915-017-0350-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for potency differences between GDF8 and GDF11

Abstract: BackgroundGrowth/differentiation factor 8 (GDF8) and GDF11 are two highly similar members of the transforming growth factor β (TGFβ) family. While GDF8 has been recognized as a negative regulator of muscle growth and differentiation, there are conflicting studies on the function of GDF11 and whether GDF11 has beneficial effects on age-related dysfunction. To address whether GDF8 and GDF11 are functionally identical, we compared their signaling and structural properties.ResultsHere we show that, despite their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
167
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(188 citation statements)
references
References 98 publications
14
167
1
6
Order By: Relevance
“…The individual mature GF protomers also overlay well with the structure of myostatin bound to follistatin 288 (PDB: 3HH2, Cα RMSD: 0.63 Å, 65 atoms), but exhibit a shift in inter‐protomer angle (Fig C; Cash et al , ). This observation is consistent with that of Walker et al , who recently showed that the mature myostatin GF dimer crystallises with radically different inter‐protomer angles in apo and FST‐288 bound states (Fig C; Walker et al , 2017a). Conformational plasticity is similarly well documented for activin A, which has inter‐protomer angles ranging from 50° in complex with type II receptor ecto‐domain (PDB: 1NYS), to 108° when bound to FST‐315 (PDB: 2P6A; Wang et al , ).…”
Section: Resultssupporting
confidence: 92%
“…The individual mature GF protomers also overlay well with the structure of myostatin bound to follistatin 288 (PDB: 3HH2, Cα RMSD: 0.63 Å, 65 atoms), but exhibit a shift in inter‐protomer angle (Fig C; Cash et al , ). This observation is consistent with that of Walker et al , who recently showed that the mature myostatin GF dimer crystallises with radically different inter‐protomer angles in apo and FST‐288 bound states (Fig C; Walker et al , 2017a). Conformational plasticity is similarly well documented for activin A, which has inter‐protomer angles ranging from 50° in complex with type II receptor ecto‐domain (PDB: 1NYS), to 108° when bound to FST‐315 (PDB: 2P6A; Wang et al , ).…”
Section: Resultssupporting
confidence: 92%
“…The growth factor dimer adopts a closed conformation in pro‐TGF‐β1 (pdb: 3RJR) (K) (Shi et al , ) and pro‐BMP9 (pdb: 4YCG) (L) (Mi et al , ), and an open conformation in pro‐GDF8 (pdb: 5NTU). N–PCrystal structures of the GDF8 growth factor in different conformations. The apo form (pdb: 5JI1) (Walker et al , ) adopts an open conformation (N). In contrast, the GDF8 growth factor adopts a closed conformation when in complex with the antagonist FSL3 (O) (pdb: 3sek) (Cash et al , ) and yet another conformation when bound to Fab (P) (pdb: 5f3b) (Apgar et al , ). Source data are available online for this figure.…”
Section: Resultsmentioning
confidence: 99%
“…If the GF in the pro‐activin A complex had a closed conformation, as seen in some activin GF complex structures with inhibitors and receptors, the pro‐complex would have to assume a markedly more obtuse V‐angle (Hinck et al , ; Wang et al , ). Notably, the apo GDF8 GF dimer structure adopts an open GF conformation (Fig N; Walker et al , ) with a more acute V‐angle than in the pro‐complex (Fig M), whereas crystal structures of the GDF8 GF in complex with antagonists reveal a closed conformation and a complex with Fab reveals yet another conformation (Fig O and P; Apgar et al , ; Hinck et al , ). Our HDX results showed no changes in GDF8 GF regions that alter in conformation between the open and closed GF conformations, including the GF α3′‐helix (Hinck et al , ), and thus provided no evidence for a change in overall GF conformation associated with TLL2 cleavage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations